Real-time fluid flow movement identification in porous media for reservoir monitoring application using polycarbonate optical fibre Bragg grating sensor - Moslan, Mohd Shahrizan; Othman, Mohd Hafiz Dzarfan; Samavati, Alireza; Theodosiou, Antreas; Kalli, Kyriacos; Ismail, Ahmad Fauzi; Rahman, Mukhlis A. (My University, 2023)
Fibre optic sensing technology has recently been hailed as a viable alternative for a real-time reservoir monitoring method. The aim of this study is to develop a robust and high-sensitivity polycarbonate optical fibre (PCPOF) sensor that can detect oil movement in porous media. To enhance the sensing capability of the Bragg sensor, partial removal of the cladding and deposition of APTES treated TiO2 on the sensing region was conducted. The cladding layer was removed using the chemical etching and the etching time was varied from 5 to 11 min. The best etching time was 9 min with a cladding thickness of ∼1.47 µm and increasing the etching time may result in damage to the fibre core. The nanoparticles were coated evenly to the sensing areas through a double dip-coating technique to ensure uniform distribution of TiO2. Sensor sensitivity was tested at 60 °C, 90 °C, and 120 °C. The sensitivity of the sensor was found to be more than 100 nm/RIU on average in different temperatures and the sensor was also capable to work at a temperature of 120 °C. Thus, the fabricated fibre optic sensor offers huge potential for real-time monitoring of reservoirs in oil and gas fields, which should be a very useful tool for engineers.
Keywords: Enhanced oil recovery; Fibre optic sensor; Oil movement detection; Reservoir monitoring